2021
DOI: 10.1101/2021.03.04.433919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Essential Role of UBXN3B in B Lymphopoiesis

Abstract: Hematopoiesis is finely regulated to enable timely production of the right number and type of mature immune cells to maintain tissue homeostasis. Dysregulated hematopoiesis may compromise antiviral immunity and/or exacerbate immunopathogenesis. Herein, we report an essential and new role of ubiquitin X domain containing gene 3B (UBXN3B) in balancing myelopoiesis and lymphopoiesis. Ubxn3b deficiency (Ubxn3b−/−) results in a remarkable increase in myeloid cells and neutrophil-to-lymphocyte ratio, along with a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 69 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Despite these recent advances, we still know very little about the roles of CNS fibroblasts in the development and maintenance of the healthy, adult CNS and how they contribute to disease aside from fibrotic scarring. While we focus mostly on rodent studies in this Review, perivascular fibroblasts have been detected in human tumour samples 5 and associated with the vasculature of the human brain 6 , 7 , confirming that these cells are indeed present in the human CNS. Furthermore, perivascular fibroblasts have been shown to be dysfunctional in patients with amyotrophic lateral sclerosis (ALS) 8 .…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Despite these recent advances, we still know very little about the roles of CNS fibroblasts in the development and maintenance of the healthy, adult CNS and how they contribute to disease aside from fibrotic scarring. While we focus mostly on rodent studies in this Review, perivascular fibroblasts have been detected in human tumour samples 5 and associated with the vasculature of the human brain 6 , 7 , confirming that these cells are indeed present in the human CNS. Furthermore, perivascular fibroblasts have been shown to be dysfunctional in patients with amyotrophic lateral sclerosis (ALS) 8 .…”
Section: Introductionmentioning
confidence: 87%
“…To better define the molecular characteristics of perivascular and pial fibroblasts, single-cell RNA sequencing of fibroblasts isolated separately from adult leptomeninges and brain will be required. However, a recent preprint study reporting vessel isolation and nuclei extraction for sequencing (VINE-seq) in humans used annotations from other sequencing studies to detect distinct clusters of perivascular and meningeal fibroblasts 6 and found enriched expression of ECM components in perivascular fibroblasts whereas meningeal fibroblasts showed enriched expression of solute transporters 6 .…”
Section: Cns Fibroblast Origins and Diversitymentioning
confidence: 99%
See 1 more Smart Citation